السياسة الرياضية لثقافة الجسد دراسة في علم الاجتماع - ناظر حميد بشير (Al-Adab Journal, 2018)
Sports is today a global phenomenon that concerns all societies, and is one of the most important manifestations of the movement associated with the human body, and through the body can the athlete to send a lot of messages, which is not spoken, carries many social, cultural and national meanings. The new sports policy is mainly aimed at developing and practicing sport at the level of the individual and society. This requires knowledge of all aspects of the structure, development and rooting. Based on this, the culture of the body is revealed as a tributary of sports culture that promotes society and preserves social values ​​and customs within a particular sports policy. Through sports policy we can say that sports policy is a tool of social control by instilling conservative values ​​and directing the behavior of individuals in a way that ensures the preservation of these values ​​through the body and deepen loyalty and belonging to the political and sports system, and some mechanisms of sports policy clubs and federations The Olympic Committee and others are the basic sports devices in the local community, which are complementary elements of each other and linked to each other, and has a significant role in emphasizing the need to preserve the body within the culture of sport is the goal of community development, Citizenship through external sports participations.